Evaluating the effectiveness of water infrastructures for increasing groundwater recharge and agricultural production – a case study of Gujarat, India - Chinnasamy, Pennan; Misra, Gourav; Shah, Tushaar; Maheshwari, B.; Prathapar, Sanmugam A. (Elsevier, 2015)
Groundwater for agricultural purposes is of utmost importance in the Indian state of Gujarat. To augment existing agricultural water resources, the Gujarat Government invested in many large-scale and smallscale water infrastructures (WI). In order to increase water storage and groundwater recharge and to justify further investments in WI, a better understanding on the impacts of past WIs is needed. This study uses data from NASA’s Gravity Recovery and Climate Experiment (GRACE), along with soil moisture data from the Global Land Data Assimilation Systems, to estimate water storage before and after the intensification in the investment in WIs. In addition, Normalised Difference Vegetation Index (NDVI) data from the Moderate Resolution Imaging Spectrometer (MODIS) sensor was used to show changes in seasonal cropped areas during the same period. The analysis of data showed that the water storage in the state was estimated to be 24 BCM in 2003–2004 and 30 BCM in 2010–2011, an increase of 29% pre and post WI intensification. The Pixel Crop Duration Index (PCDI) indicated an increase in cropped area (at district level) in 2010–2011 when compared with 2003–2004 period, by 30% on yearly basis and about 80% during non-monsoon period. Results also indicates a significant net increase in water storage (by 5890 M m3 after water used for crop intensification) and increase in agricultural crop area (by 63,862 km2) in Gujarat during the period of intensification in infrastructures for water storage and groundwater recharge. Results also indicate that some districts have higher net water storage (compared to 2003), however the cropped area duration - PCDI has not increased much (e.g., Valsad and Navsari). The findings of this study can increase the understanding of the potential of WIs and provide valuable guidance for increasing cropped area in high water storage regions of Gujarat.